1980
DOI: 10.1002/1520-6807(198001)17:1<128::aid-pits2310170124>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Educational personnel's perceptions of mainstreaming and resource room effectiveness

Abstract: Equivalent forms of a questionnaire were administered to elementary classroom and resource room teachers. The questionnaires were designed to elicit teachers' attitudes and perceptions as to the effectiveness and appropriateness of mainstreaming, regular classroom teachers' level of skill competency, assistance from the resource room, and communication between the resource room and regular classroom teachers. Results indicated that resource and regular teachers evidenced differential perceptions as to all fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…In a study of 23 resource teachers and 144 classroom teachers, Graham, Hudson, Burdg, and Carpenter (1980) found that resource teachers felt adequate lines of communciation existed between classroom teachers and themselves, while classroom teachers felt that this was not the case at all. D' Alonzo and Wiseman (1978) surveyed 134 high school learning disability resource room teachers and reported that role expectations were relatively unestablished in areas contingent upon shared efforts: referrals, in-service, classroom observations, consultation, and team teaching.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 23 resource teachers and 144 classroom teachers, Graham, Hudson, Burdg, and Carpenter (1980) found that resource teachers felt adequate lines of communciation existed between classroom teachers and themselves, while classroom teachers felt that this was not the case at all. D' Alonzo and Wiseman (1978) surveyed 134 high school learning disability resource room teachers and reported that role expectations were relatively unestablished in areas contingent upon shared efforts: referrals, in-service, classroom observations, consultation, and team teaching.…”
mentioning
confidence: 99%
“…The success of any mainstreaming effort is subject to the cooperation and attitudes of the individuals involved (Graham et al 1980), yet little research has been done on the perceptions of both special and regular educators with regard to resource room teachers. Most classroom teachers and school administrators have or will have contact with students receiving services in a resource room program.…”
mentioning
confidence: 99%
“…The· likelihood of writing success is increased if each of the participating teachers is assigned specific responsibilities for selected aspects of the proposed composition program. This requires that special and regular classroom teachers establish effective lines of communication, work together cooperatively, and coordinate their instructional plans ( Graham, Hudson, Burdg, & Carpenter, 1980;Hudson, Graham, & Warner, 1979). The author, therefore, hopes that teachers will adapt the model presented in this article to their own particular students and situations.…”
Section: Resultsmentioning
confidence: 99%
“…A substantial body of evidence confirms the seriousness of this problem. Some teachers are uncomfortable with mainstreamed children, resent their presence, and treat them differently from their peers (Graham, Burdig, Hudson, & Carpenter, 1980;Schmelkin, 1986); some classmates reject mainstreamed children or socially segregate them (Gottlieb, 1975;Gresham, 1986;Willey & McCandless, 1973); Many mainstreamed children, who often have lower self-esteem than their counterparts in special classes, have difficulties (Barger, 1978;Semmel & Semmel, 1979) and only occasionally show evidence of superior achievement in regular classes (Strain & Kerr, 1981, p. 37). Too frequently it appears that mainstreaming practices result in "parallel streams" of education for the handicapped and nonhandicapped children placed in common classroom settings (Gerold & Barners, 1985).…”
Section: Ruth C Westmentioning
confidence: 97%